Proportion of different anxiety disorders among outdoor patients attending a tertiary care psychiatry hospital (Bangladesh Journal of Psychiatry, 2020)
As a common psychiatric disorder, anxiety disorder considerably impaired the mental wellbeing and functioning of an individual. This study aimed to estimate the proportion of different anxiety disorders among outdoor patients attending a tertiary care psychiatry hospital in Dhaka, Bangladesh. It was a descriptive cross-sectional study conducted among 150 conveniently recruited outdoor patients attending in National Institute of Mental Health (NIMH) from July 2018 to February 2023. Diagnosis of anxiety disorder was made clinically by consultant psychiatrist of NIMH outpatient department and sociodemographic data was collected by a semi-structured questionnaire through face to face interview. Data analysis was performed by statistical package for social sciences (SPSS) 23. The results showed that the most common diagnosis was generalized anxiety disorder (36.7%) followed by mixed anxiety and depressive disorder (20%) and panic disorder (15.3%). Most respondents were male (52%), urban habitants (80.7%), students (32%) and had completed honors and higher than honors education (42%) where the mean (±SD) age of the participants was 29.05 (±8.26) years. The study provided useful information regarding the proportions of different anxiety disorders and their characteristics which was expected to guide better management of this psychiatric condition as well as in-depth research in the future.Bang J Psychiatry 2020; 34(2): 30-32